Performance identification of the asynchronous electric drives by the spectrum of rotor currents - Vladimir L. Kodkin; Aleksandr Sergeevich Anikin; Aleksandr A. Baldenkov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The efficiency of analyzing the rotor currents of asynchronous electric drives with frequency control is substantiated in the article. To assess the quality of torque generation in the engine it is suggested to use the spectral analysis of these currents and the fundamental harmonic, as the most accurate "conformity" of slip in an asynchronous motor. The proposed method showed that "sensorless vector" control leads to the appearance of high-frequency harmonics with significant amplitude. Because of these harmonics, a non-sinusoidal electromagnetic moment is created and the performance of the drive is decreased. The most effective method of torque generation is the frequency control with positive stator current feedback. This control is dominated by pronounced harmonic components, which indicates the proximity of this structure to linear and significantly better controllability of the drives, which makes promising their use in high-tech mechanisms, in particular, in industrial robots. Simulation and experiments confirm the proposed theoretical propositions.